Kepemimpinan Nyai dalam Memelihara Kajian Kitab Kuning di Ma’had Aly Nurul Jadid Probolinggo - Viki Amalia; Zainal Arifin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
Nyai (wife of Kiai/pesantren leader) holds an essential role in pesantren management, particularly pertaining to the process of taking care of and nurturing the pesantren tradition. This research investigates leadership typology of Nyai Nur Latifah in Ma’had ‘Aly Nurul Jadid Probolinggo in maintaining Kitab Kuning studies. Employing phenomenological approach of qualitative study, this research collect the data through observation, indepth interview, and documentation. This research found that: (1) the leadership type of Nyai Nur Latifah in preserving Kitab Kuning studies can be categorized as democratic and charismatic; (2) there are two factors supporting her leadership: internal factors (religious competence and technological application ability), and external factors (support from family council, special assembly for Kitab Kuning, and the guidance in Kitab Kuning reading (BMK), whereas, the challenging factors are related to internal situation such as multiple roles as the leader of Fatayat NU and recitation, as well as external factors such as the decreased preference of students to learn Kitab Kuning and the negative impact of technology.